The Effect Of Competency, Independence, Ethics Auditor And Professionalism To The Audit Quality And Emotional Intelligence As A Variable Of Moderation - Yeni Kumalasari; Muhaimin Dimyati; Ratih Rachmawati (ABM: International Journal of Administration, Business and Management, 2019)
This study aims to determine the competence, independence, ethics of auditors and professionalism on audit quality and emotional intelligence as a moderation variable. (1) To obtain empirical evidence and analyze about the influence of competence, independence, auditor ethics, professionalism simultaneously on audit quality. (2) To obtain empirical evidence and analyze about the influence of competence, independence, auditor ethics, partially on audit quality. (3) To obtain empirical evidence and analyze the effect of emotional intelligence on the relationship between competence, independence, auditor ethics, professionalism on audit quality. This study uses moderate regression analysis method using SPSS Windows 22. The results in this study indicate that Competence has no effect on audit quality, Independence has an effect on audit quality, Auditor Ethics does not affect audit quality and Professionalism does not affect audit quality, Emotional Intelligence Relationship between Competence, Independence, Auditor Ethics and Professionalism to Quality audit. An independent auditor will provide a tangible assessment of the financial statements, without any burden to any party, so the resulting judgment will reflect the actual conditions of the client being examined. Keywords: Auditor Ethics, Professionalism, Emotional Intelligence, Audit Quality